A theoretical framework on exploring the implementation of digital entrepreneurship education in Malaysian polytechnics' business incubation program - Rosli, Nur Syahirah; Abdul Kadir, Suhaida; Jamaluddin, Rahimah; Sufian Kang, Enio Kang Mohd (Human Resource Management Academic Research Society, 2023)
The integration of digital technologies like cloud computing, social media, and the Internet of Things has transformed the current entrepreneurial processes. This shift has prompted education sectors to incorporate digital entrepreneurship as a revolutionary force into their curriculum. However, the acceptance of digital technology and its subsequent integration into entrepreneurship education in higher education institutions has been perceived as challenging. In the Malaysian context, polytechnics have been urged to respond quickly to technological changes through their business incubation program to equip students with the skills required for the evolving human-machine cooperation era. It is vital to emphasize that the existing digital education frameworks are not directly linked to address digital entrepreneurship education's specific demands in the TVET institutions. This study aims to explore the emerging concept of the implementation of digital entrepreneurship education in business incubation programs from multiple disciplinary perspectives. This paper develops a theoretical framework to study digital entrepreneurship education drawing from established theories and model, including institutional isomorphism theory, new venture theory, and the Student Entrepreneurship Encouragement Model (Jansen et al., 2015). This paper has formulated four fundamental research questions derived from the theoretical framework, thus leading to a better understanding of the practice of digital entrepreneurship education in Malaysian polytechnics.